Analysis of Factors Influencing Open Defecation Behavior in Coastal Areas of Indonesia: A Review - Listy Handayani; Rini; Inochi Lara Palino (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Open defecation free (ODF) status is essential for protecting both environmental quality and public health. Open defecation, which refers to the practice of defecating in open spaces such as rice fields, forests, rivers, beaches, or the sea, can inadvertently contaminate water sources and soil, posing serious health risks. In Indonesia, access to improved sanitation has shown progressive improvement, with the national open defecation rate decreasing from 7.61% in 2019 to 6.19% in 2020, and further declining to 5.69% in 2021. Despite this progress, open defecation remains a persistent issue, particularly in coastal regions. Objective: This study aims to explore the factors associated with open defecation behavior in coastal areas of Indonesia. Methods: A qualitative literature review method was employed to synthesize findings from relevant studies. National publications were retrieved using the Google Scholar database with the keyword